Failure or Success: Reading the Effectiveness of Legislative Regulations and Reasoning Forest Area Losses in Turkey through a Quantitative Research - Secilmisler, Tore; Ozugul, Mehmet Doruk; Yerliyurt, Bora (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2016)
Today Global Warming is an emerging issue which is also a popular research topic for urban planning. Having several reasons, deforestation is one of the major parameters that cause global warming. Legislative and governmental tools such as laws, planning, etc. are expected to serve in the scope of conserving natural assets. This article aims to examine in what extent these tools are effective in forest conservation practice. From this perspective a quantitative evaluation is carried out in order to determine this issue where provinces are accepted as research units. Nine independent variables were observed to explain the change on the dependent variable (namely 'loss of forest area of provinces') by using correlation coefficients and multiple regression analysis. As a result two basic outcomes have appeared. Firstly, related legislations mentioned in the study do not serve to a holistic conservation purpose in Turkey. Secondly, independent variables explain the loss of forest areas in the level of (R-2 : 0.548) 55%.
Keywords: Deforestation; legislative regulations; Turkey; Architecture